2002
DOI: 10.1103/physrevb.65.165115
|View full text |Cite
|
Sign up to set email alerts
|

Ab initioelectronic structure calculations for metallic intermediate band formation in photovoltaic materials

Abstract: A metallic isolated band in the middle of the band gap of several III-V semiconductors has been predicted as photovoltaic materials with the possibility of providing substantially enhanced efficiencies. We have investigated the electronic band structures and lattice constants of Ga n As m M and Ga n P m M with MϭSc, Ti, V, and Cr, to identify whether this isolated band is likely to exist by means of accurate calculations. For this task, we use the SIESTA program, an ab initio periodic density-functional method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(77 citation statements)
references
References 30 publications
3
70
0
4
Order By: Relevance
“…Since 2002, ab initio band calculations in our group have suggested that certain transition metals could form an IB in III-V [75] compounds. More recently, V-added In 2 S 3 with high concentration of V (V 2 In 14 S 2 4) has been prepared by solvo-thermal synthesis.…”
Section: Transition Metals Derived From Ab Initio Calculationsmentioning
confidence: 99%
“…Since 2002, ab initio band calculations in our group have suggested that certain transition metals could form an IB in III-V [75] compounds. More recently, V-added In 2 S 3 with high concentration of V (V 2 In 14 S 2 4) has been prepared by solvo-thermal synthesis.…”
Section: Transition Metals Derived From Ab Initio Calculationsmentioning
confidence: 99%
“…In our group, we have proposed some transition metal doped semiconductors (TMS) [6][7][8][9] as intermediate band materials. These earlier works [8,9] have revealed that the insertion of Ti into a chalcopyrite semiconductor such as CuGaS 2 , with a band-gap found experimentally as 2.53 eV [10] depicts a separated intermediate band.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, certain solar cell types and, in particular, the intermediate band solar cells 1 ͑IBSCs͒-in which electron-hole pairs are created out of sub-band-gap photons by means of quantum dots 2 ͑QDs͒ or by alloys of different types [3][4][5] -absorb weakly the sub-band-gap photons because of the low density of absorbing centers ͑below 10 17 cm −3 in the QD-IBSC͒. It is to be noted that most probably QD-IBSC will not be practical unless they can utilize a good scheme of light-absorption intensification.…”
Section: Introductionmentioning
confidence: 99%